Optical tweezers assisted surface plasmon resonance imaging of biological cells at nm resolution - Yuan, Larry Xiao Cong. (2010)
Surface plasmon resonance imaging (SPRi) is an emerging optical technique for imaging low contrast samples at nm resolution. Since the vertical resolution of the surface plasmons extends from sub-nanometer to hundreds of nanometers, SPRi is potentially useful for the real-time monitoring of transport processes, trafficking processes and surface interactions of cell membranes and tissues. The understanding of cell biology is gaining huge global interests as biologists, researchers and doctors attempt to understand cells' proliferation, find treatment for various diseases and monitor intracellular trafficking, to mention a few.